2020
DOI: 10.1051/epn/2020104
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disks around young stars: the cradles of planet formation

Abstract: Protoplanetary disks around young stars are the birth sights of planetary systems like our own. Disks represent the gaseous dusty matter left after the formation of their central stars. The mass and luminosity of the star, initial disk mass and angular momentum, and gas viscosity govern disk evolution and accretion. Protoplanetary disks are the cosmic nurseries where microscopic dust grains grow into pebbles, planetesimals, and planets. Protoplanetary Disks as Analogues of Young Solar Systems

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…From the Gaia CMD analysis we found that all the co-moving stars are coeval with IL Cep and they are PMS stars in the age range 0.1 -1 Myr. The stars with ages of a few Myr should be actively accreting from its circumstellar disk (Furlan et al 2011;Semenov & Teague 2020). The accreting young stars will show infrared excess in their spectral energy distribution due to the thermal re-radiation from the dust in the circumstellar disk (Hillenbrand et al 1992;Malfait et al 1998).…”
Section: Identification Of Circumstellar Disk Candidatesmentioning
confidence: 99%
“…From the Gaia CMD analysis we found that all the co-moving stars are coeval with IL Cep and they are PMS stars in the age range 0.1 -1 Myr. The stars with ages of a few Myr should be actively accreting from its circumstellar disk (Furlan et al 2011;Semenov & Teague 2020). The accreting young stars will show infrared excess in their spectral energy distribution due to the thermal re-radiation from the dust in the circumstellar disk (Hillenbrand et al 1992;Malfait et al 1998).…”
Section: Identification Of Circumstellar Disk Candidatesmentioning
confidence: 99%